GENDER AND AGE CHARACTERISTICS OF THE PREVALENCE OF HYPERCHOLESTEROLEMIA IN THE POPULATION - Hajiyeva, Y.H.; Aghayev, A.A. (World of Medicine and Biology, 2022)
The purpose of the study was to assess the distribution of hypercholesterolemia in the population according to gender and age characteristics. Cholesterol-metry was conducted among 2013 random residents; 887men and 1126 women were involved in the study. After appropriate clarifications and on a voluntary basis, blood was taken from the respondents to study the content of cholesterol. According to the results of cholesterol-metry, the normal level of cholesterol was found in 21.4±0.9 % of city residents, its elevated level was correspondingly in 28.3±1.0 % (t=5.04; P0.05) and very high level in 19.7±0.9 % (t=8.07; P